The Business Structure of Japan's Electric Industry for 1963-2016: Analysis on the Revenues and Expenditures throughout before and after the “Deregulation” - Aoki, Hidekazu; Kawamiya, Nobuo (International Journal of Energy Economics and Policy, 2018)
The Federation of Electric Power Companies (FEPC) of Japan has long been releasing the detailed financial statements of their member corporations (on their web site). We have analyzed the FEPC's financial data over half a century and have clarified the problems and distortions built in Japan's power industry through the ‘dual pricing mechanism' for the “industrial use” and the “home-use” sectors. In fact the former shares two thirds of the power demand and yields only small profits or even losses; and the latter, sharing one third of the demand, yields nearly all of the industry's profits. After the full retail deregulation, however, this home-use sector (the industry's treasure box) seems now suffering diminution of profitability: because the power majors have began to raise a “cutthroat competition” against each other. This price-cutting war might be considered very dangerous for the sustainability of this industry because this business is highly equipment-intensive and so severely vulnerable to any revenue instability. Keywords: Electricity demand, Dualistic pricing, Income statement, Power retail deregulation JEL Classifications: M4, L5, L9, Q4 DOI: https://doi.org/10.32479/ijeep.6999